Wileńskie Szopki Akademickie jako zjawisko artystyczne w środowisku Wydziału Sztuk Pięknych Uniwersytetu Stefana Batorego w Wilnie - Kania, Agnieszka (Saeculum Christianum. Pismo Historyczne, 2019)
The article concerns Vilnius Academic Nativity Scenes, which were created in 1921-1926 in the environment of the Faculty of Fine Arts of the Vilnius University. Performances were created by both academic teachers and students. Nativity scenes were satirical and divided into two parts: traditional and current. The article presents the silhouettes of the creators of the Nativity Scenes, as well as their influence on the character of the performances. It also depicts the main themes of Nativity Scenes, such as: aspects of academic life, conflicts in the artistic milieu of Vilnius, as well as important political and cultural events. The article aims to present the importance of Academic Nativity Scenes in the Vilnius University milieu, as well as in the cultural life of the city.